2019
DOI: 10.1177/0886260519888526
|View full text |Cite
|
Sign up to set email alerts
|

Which Factors Are Associated With Adolescent Reports of Experiencing Various Forms of Abuse at the Family Level in Post-Conflict Northern Uganda?

Abstract: Research assessing familial violence against adolescents, using caregiver–adolescent dyads, is limited in post-conflict settings. This study aimed to determine the prevalence and factors associated with adolescent-reported familial abuse in post-conflict northern Uganda. It also assessed the relationship between abuse subtypes and (a) beliefs supporting aggression and (b) adolescent well-being and life satisfaction. A randomly selected community-based sample of 10- to 17-year-old adolescents (54% girls) and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Regarding the types of victimization included in the polyvictimization construct (Supplementary Appendix A), both specific domain and individual items of victimization differed widely. To iterate, the number and the types of victimization included in polyvictimization constructs varied extensively from using two victimization types with three individual items (Shevlin et al, 2015) to three victimization types with 14 items (Natukunda et al, 2019), 36 individual victimization items grouped into six broader types (Álvarez-Lister et al, 2014), 44 victimization items of 10 types (Michel-Smith, 2019), and to 75 items of 10 different types of victimization (Riedl et al, 2019). At times, direct violence exposure was classified as one type (Voith et al, 2014), while, at other times, direct violence exposure was often further classified into more detailed victimization types, such as sexual violence, physical violence, or conventional crime (e.g., Aho et al, 2016; Kirchner et al, 2020; Turner et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the types of victimization included in the polyvictimization construct (Supplementary Appendix A), both specific domain and individual items of victimization differed widely. To iterate, the number and the types of victimization included in polyvictimization constructs varied extensively from using two victimization types with three individual items (Shevlin et al, 2015) to three victimization types with 14 items (Natukunda et al, 2019), 36 individual victimization items grouped into six broader types (Álvarez-Lister et al, 2014), 44 victimization items of 10 types (Michel-Smith, 2019), and to 75 items of 10 different types of victimization (Riedl et al, 2019). At times, direct violence exposure was classified as one type (Voith et al, 2014), while, at other times, direct violence exposure was often further classified into more detailed victimization types, such as sexual violence, physical violence, or conventional crime (e.g., Aho et al, 2016; Kirchner et al, 2020; Turner et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…A second approach to the categorical variable (7.29%) was to define polyvictimization as experiencing more than one type of violence (e.g., Charak et al, 2015; Hickman et al, 2013; Itani et al, 2018; Kamndaya et al, 2017; Natukunda et al, 2019; Sabri et al, 2012; Shevlin et al, 2015; Updegrove & Muftic, 2019). These studies compared the polyvictimization group with those who experienced none or one type of violence.…”
Section: Resultsmentioning
confidence: 99%
“…Unsparingly, the current study showed that the most reported forms of victimization by adolescents were: caregiver victimization, conventional crime, and witnessed/indirect victimization. Secondly, the two decades of armed conflict (1986–2006) between the Lord’s Resistance Army (LRA) and the Ugandan government could have negatively impacted adolescents’ exposure to victimization [ 51 ] by fostering beliefs and traditions that support corporal punishment to discipline children [ 57 ]. Hence, the beliefs, traditions and practices that perpetuate corporal punishment against children need to be strongly discouraged through targeted education, dialogue, and implementation of the national law against corporal punishment.…”
Section: Discussionmentioning
confidence: 99%